Status Epilepticus Due to Organophosphate Poisoning in an Infant - Parmar, PN (Journal of Nepal Paediatric Society, 2015)
We report a case of a three months old female presented with status epilepticus who was diagnosed as organophosphate (OP) poisoning. She was from rural area with agricultural background. Typical clinical features and history of exposure to organophosphate compound were absent. The infant was successfully treated with atropine, pralidoxime and supportive management. Safety and efficacy data of pralidoxime in infants are limited in literature and was found safe in our case. J Nepal Paediatr Soc 2014;34(3):247-249 DOI: http://dx.doi.org/10.3126/jnps.v34i3.10497